Syntactic complexity differentially affects auditory sentence comprehension performance for individuals with age-related hearing loss - Shin, Junyoung; Noh, Shinhee; Park, Jimin; Sung, Jee Eun (Frontiers in Psychology, 2023)
Objectives: This study examined whether older adults with hearing loss (HL) experience greater difficulties in auditory sentence comprehension compared to those with typical-hearing (TH) when the linguistic burdens of syntactic complexity were systematically manipulated by varying either the sentence type (active vs. passive) or sentence length (3-vs. 4-phrases).Methods: A total of 22 individuals with HL and 24 controls participated in the study, completing sentence comprehension test (SCT), standardized memory assessments, and pure-tone audiometry tests. Generalized linear mixed effects models were employed to compare the effects of sentence type and length on SCT accuracy, while Pearson correlation coefficients were conducted to explore the relationships between SCT accuracy and other factors. Additionally, stepwise regression analyses were employed to identify memory-related predictors of sentence comprehension ability.Results: Older adults with HL exhibited poorer performance on passive sentences than on active sentences compared to controls, while the sentence length was controlled. Greater difficulties on passive sentences were linked to working memory capacity, emerging as the most significant predictor for the comprehension of passive sentences among participants with HL.Our findings contribute to the understanding of the linguistic-cognitive deficits linked to age-related hearing loss by demonstrating its detrimental impact on the processing of passive sentences.Cognitively healthy adults with hearing difficulties may face challenges in comprehending syntactically more complex sentences that require higher computational demands, particularly in working memory allocation.